Analysis of Students’ Interpersonal Communication Barriers in a Gender-Segregated Environment: Case Study at Madrasah Aliyah Negeri Palu - Munif, Muhammad; Alimuddin, Nurwahida; Sabir, Sabir; Siti Rahmi (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
Students’ interpersonal communication skills play an essential role in the success of social interactions. This study aims to analyze the barriers to interpersonal communication in students at Madrasah Aliyah Negeri Palu, with a focus on students of the main subject. The method employed was a qualitative case study, involving one key informant and two supporting informants. Data was collected through in-depth interviews and documentation, then analyzed using Miles and Huberman’s models: data reduction, data presentation, and conclusions drawn. The results showed that low interpersonal communication was influenced by a religion-based education system that implemented gender segregation and a lack of interaction between school residents. This condition hinders the process of getting to know each other between students. However, some students are still able to adjust personally and academically. The novelty of this research lies in the local context, namely the social dynamics in Islamic schools with gender separation, which provides a new understanding of the influence of culture and educational structure on students’ interpersonal communication. Keywords: barriers, gender, communication, student, interpersonal